The clinical and molecular genetic approach to Duchenne and Becker muscular dystrophy: an updated protocol. Issue 10 (October 1997) - van Essen, A J; Kneppers, A L; van der Hout, A H; Scheffer, H; Ginjaar, I B; ten Kate, L P; van Ommen, G J; Buys, C H; Bakker, E
Abstract : Detection of large rearrangements in the dystrophin gene in Duchenne and Becker muscular dystrophy is possible in about 65-70% of patients by Southern blotting or multiplex PCR. Subsequently, carrier detection is possible by assessing the intensity of relevant bands, but preferably by a non-quantitative test method. Detection of microlesions in Duchenne and Becker muscular dystrophy is currently under way. Single strand conformational analysis, heteroduplex analysis, and the protein truncation test are mostly used for this purpose. In this paper we review the available methods for detection of large and small mutations in patients and in carriers and propose a systematic approach for genetic analysis and genetic counselling of DMD and BMD families, including prenatal and preimplantation diagnosis.